Skeletal muscle fatigue does not affect shooting accuracy of handball players - Akyüz, B.; Avsar, P. A.; Bilge, M.; Deliceoglu, G.; Korkusuz, F. (Isokinetics and Exercise Science, 2019)
BACKGROUND: Shooting accuracy and ball speed are important factors relating to scoring in handball that could be affected by skeletal muscle fatigue. OBJECTIVE: To explore the effects of muscle fatigue on male handball players` shooting accuracy and ball speed. METHODS: Sixteen elite handball players (M age = 17.1 ± 1.7 years) participated in the laboratory and the field-testing sessions. Running speeds equal to 75% of participants` maximal oxygen uptake (VO2max) values from laboratory tests were used as the initial velocity for the 30-15 intermittent fitness test (30-15 IFT ) in the fatigue protocol. Participants shot to the target at random visual signals placed behind the target before and after fatigue. In order to measure wrist acceleration and ball speed, an accelerometer and a radar gun are used respectively and numbers of accurate and inaccurate shots also recorded. RESULTS: There were no significant differences between pre-fatigue and post-fatigue protocols in terms of accurate and inaccurate shots, and ball speed. Only wrist acceleration in the Y axis (M pre - fatigue = 33.12, SD = 1.17msec; M post - fatigue = 34.50, SD = 1.21msec) was affected by the fatigue protocol in inaccurate shots (p = 0.042). CONCLUSIONS: Muscular fatigue does not affect shooting accuracy and ball speed in male handball players.